The Role of Motivation on Employee Performance With Work Environment Mediaton - Rahayu, Muji (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to test whether the work environment variable acts as a mediator in the relationship between employee motivation and performance. The population in this study were employees of Survey Center X located in Bandung. The determination of the number of samples was carried out using probability random sampling techniques and calculations based on the Slovin formula, so that the number of samples was 111 respondents. Data collection was carried out by distributing questionnaires to predetermined respondents. The collected data were then analyzed using the Process Macro Hayes mediation analysis method. The results of the hypothesis test showed that the indirect effect of motivation on employee performance through the work environment was significant and had a larger coefficient than the direct effect. This finding shows that the work environment is proven to significantly mediate the relationship between motivation and performance, so that the existence of a conducive work environment can improve employee performance optimally.